Childhood Trauma increases suicidal behaviour in a treatment-resistant depression population: a FACE-DR report. (March 2021) - Yrondi, Antoine; Vaiva, Guillaume; Walter, Michel; D Amato, Thierry; Bellivier, Frank; Bennabi, Djamila; Bougerol, Thierry; Camus, Vincent; Doumy, Olivier; Genty, Jean-Baptiste; Haffen, Emmanuel; Holtzmann, Jérôme; et al.
Abstract: Objective: In addition to heredity, exposure to early-life adversity is an important predisposing risk factor of suicidal behaviour. Although the association between Childhood Trauma (CT) and suicide risk is well documented, interactions between CT and suicidal behaviour in Treatment-Resistant Depression (TRD) populations have received little coverage. This study aimed to evaluate i) association between CT and suicidal behaviour in a TRD population, and ii) the role of personality traits and impulsiveness as potential factors of mediation in these associations. Methods: Patients were recruited from a cohort of the French network of TRD expert centers. Depressive symptom severity, CT, suicidal behaviour, personality traits, and impulsiveness were assessed with the Montgomery-Åsberg Depression Rating Scale (MADRS), the Childhood Trauma Questionnaire (CTQ), the Columbia Suicide Severity Rating Scale (CSSRS), the Structured Clinical Interview for DSM-IV, the Big Five Inventory, and the Barratt Impulsivness Scale (BIS) respectively. Results: Among the 256 patients with a baseline CTQ, in relation to suicide risk for the current depressive episode, we found an association with the total CTQ scores mediated by the intensity of the current episode in a model adjusted for age and sex (total effect: β = 0.171; p = 0.011, direct effect: β = 0.135; p = 0.043; indirect effect: β = 0.036; p = 0.048). Focusing on CT subtypes, we detected an association between suicide risk and physical neglect in a model adjusted for age and sex (β = 0.301; p = 0.002), without any mediation by the intensity of the current episode. There was no mediation effect from personality traits nor impulsiveness. With regards to CSSRS to assess suicidal ideation, we did not find any association with the total CTQ score and CT subtype scores. Conclusion: We report a strong association between suicidal behaviour and CT (in particular childhood physical neglect) in a TRD population.